طبقات الرواة عن جابر بن عبدالله - رضي الله عنهما - عند الإمام البخاري: دراسة إحصائية تحليلية - قصاص، غادة عقلة بادي; الشرمان، خالد محمد محمود (جامعة إربد الأهلية - عمادة البحث العلمي, 2024)
هدفت الدراسة إلى إحصاء وتحليل طبقات الرواة عن أحد الصحابة مكثري الرواية عن رسول الله -صلى الله عليه وسلم-، وهو جابر بن عبد الله-رضي الله عنهما-عند البخاري في صحيحه؛ لبيان منهج البخاري في انتقاء مروياته. إذ قام الباحثان بإحصاء ودراسة حال الرواة الذين حدثوا عن جابر بن عبد الله-رضي الله عنهما-في صحيح البخاري من حيث عددهم، وأسماؤهم، وعدد مروياتهم، وبلدانهم، وأقوال العلماء فيهم. وخلصت الدراسة إلى أن الرواة في الصحيح عن جابر بن عبد الله-رضي الله عنهما-ثلاثة وثلاثون راويا، تم تقسيمهم إلى ثلاث طبقات؛ فالطبقة الأولى والتي تميزت بتمام الضبط فقد بلغ عددهم خمسة رواة، وكانت نسبة مروياتهم بالنسبة لكل من روى عن جابر بن عبد الله-رضي الله عنهما-أقل من الثلث بقليل، وكانت أكثر من ثلثي المرويات عن جابر بن عبد الله-رضي الله عنهما-من طريق الطبقة الثانية وهم الثقات وبلغ عددهم ستة وعشرين راويا، أما الطبقة الثالثة وعددهم اثنان وهم من درجة الصدوق فلم يخرج لهم إلا اليسير من الأحاديث. This study aims to portray the classification of Hadith narrators of one of the companions who is among those who narrates the Hadith of the Messenger of Allah (may Allah’s mercy and peace be upon him) the most that is Jaber bin Abdullah (may Allah be pleased with both of them) according to Al-Bukhari in his Sahih, a statistical and analytical study. Hence, this study shows the accuracy of Al-Bukhari's approach in selecting his narratives and the credibility of presenting it over other books of hadith. This study includes talking about the narrators who reported on the authority of Jabir bin Abdullah (may Allah be pleased with both of them) in Sahih Al-Bukhari in terms of frequencies, their names, the number of their narrations, their countries and the sayings of the scholars about them. This study concludes that the narrators in the Sahih by Jabir bin Abdullah (may God be pleased with both of them) are altogether thirty three narrators, that are divided into three levels. Approximately less than one third of their narratives come from the first level, which was characterised by the completion of perfection and their number reached five narrators. While more than two thirds of their narratives come from the second level who are the trustworthy and the number reached twenty-six narrators. While the third level, he did not extract from them except a few of it, specifically two narrations only for the purpose of a supportive chain of transmitters either from a different Sahabah or the successors.
Keywords: القرآن الكريم -- علم الطبقات -- البخاري، أبو عبدالله محمد بن إسماعيل، ت. 256 هـ. -- الأنصاري، جابر بن عبدالله بن عمرو بن حرام، ت. 78 هـ